Design and Development of A Digital Soil Temperature Monitoring System Based on The Internet of Things at North Sumatra Climatological Station - Manurung, Royston; Nasution, Tulus Ikhsan; Humaidi, Syahrul; Saragih, Immanuel Jhonson A.; Hibatullah, Khindi Aufa; Situmorang, Marhaposan; Darmawan, Yahya (Journal of Applied Geospatial Information, 2023)
Soil temperature is a crucial parameter in monitoring and understanding climate and soil ecosystems. It plays a vital role in various environmental aspects, including agriculture, ecology, and geoscience. Monitoring soil temperature is necessary for planning and managing agriculture and natural resources. Currently, temporal observations of soil temperature by BMKG are limited, conducted only at 07:55, 13:55, and 18:55 local time. This limitation makes it difficult to perform detailed soil temperature analysis. This research was conducted to design a digital soil temperature monitoring device accessible via the internet. Seven DS18B20 sensors were used at depths of 0 cm, 2 cm, 5 cm, 10 cm, 20 cm, 50 cm, and 100 cm, combined with an ESP8266 module using the Arduino system. The implementation of this design resulted in a real-time soil temperature monitoring system with data updates every 10 seconds. The observed data are displayed on a 20x4 LCD and sent to the cloud, making them accessible on the webpage http://monitoringsuhutanah.my.id. Calibration results indicate that the DS18B20 sensors used in this study provide accurate and consistent temperature measurements, with an average correction range of (-0.20) to 0.24, thus suitable for operational use. Field tests show that the digital data are accurate and correspond (linearly correlate) with conventional data. This is based on a correlation value of 0.7, while the RMSE values range from 0.5 to 2.18 and the bias ranges from (-0.69) to 0.08.